DA URBANIZAÇÃO DO TERRITÓRIO AO URBANISMO DA REQUALIFICAÇÃO DOS ESPAÇOS CENTRAIS: A REPRODUÇÃO DO ESPAÇO URBANO COMO FRONTEIRA INTERNA DA EXPANSÃO CAPITALISTA - Santos, César Ricardo Simoni (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2008)
Although Brazilian cities did not undergo the process of gentrification, from 1950 to 1980, they felt the international expansion of capitalism.The inclusion of Brazilian territory in the scope of profitable business happened in accordance to its economic condition as an emerging country whose territory, from the point of view of capitalist circulation, was yet to be explored. While in the core of capitalist economy urban space, already consolidated all over the territory, attended to the demands of valorization mostly through re-qualifying of downtown areas, in Brazil new suburban areas were inserted in the circulation of capital as they expanded. It is only after the 1990’s, following the bankrupcy of the so-called ‘developmentalist’ state, that the capacity for urban expansion decreased. It was, therefore, from that decade on that the big Brazilian cities witnessed the valorization of downtown areas as a strategy for the reproduction of capital.